An operational framework for improving decentralised agricultural extension : a Ghanaian case study : a thesis submitted in partial fulfilment of the requirement for the degree of Doctor of Philosophy (Ph. D.) in Agricultural Extension, Massey University, Institute of Natural Resources, Agricultural/Horticultural Systems & Management - Okorley, Ernest (Massey University, 2007)
The pressure on the public agricultural extension organisation in Ghana to improve its responsiveness to meet the needs of farmers has increased since the globalisation of trade in the early 1990s. To improve agricultural productivity and the livelihood security of farm households, the Ministry of Food and Agriculture in Ghana decentralised its extension service in 1997. Although this was a critical change in agricultural policy, the extension service has struggled to implement this policy effectively. Further improvement in the situation is hampered because there has been little research published in this area. To provide this understanding, a single-case study of a successful decentralised district level extension organisation in Ghana was used to identify the factors, processes and outcomes that contribute to its performance. The case organisation is an example of a district agricultural extension organisation that operates under a decentralisation system at the level of deconcentration, with a high farmer-to-extension agent ratio and limited and uncertain levels of Government funding. The results of the study emphasised the importance of the effects of both external and internal (or organisational) factors on the performance of the case organisation. The external factors included: (1) the political will to decentralise, (2) the level of decentralisation of other government departments, (3) the provision of a clear legal framework for decentralisation and (4) the existence of established institutions that are willing to support the decentralisation process. New external factors that were identified in this study were (1) the type and drivers of decentralisation, (2) stakeholders' willingness and commitment to support the decentralisation process and (3) the community characteristics in terms of land tenure arrangements and gender roles. The results confirmed the importance of the organisational factors prescribed in the literature: (1) stakeholder participation, (2) managerial and technical capacity, (3) operational funding and (4) accountability. However, the study also identified five other interrelated organisational factors that influenced the success of the case organisation that had not been previously reported in the literature. These included the needs to: (1) develop a needs-based extension programme, (2) expand the extension service focus and roles, (3) foster a cross-sector pluralistic extension approach (4) use needs-based groups for service delivery, and (5) extension staff attitudinal change. Multistakeholder (farmer and other organisations) participation was critical for the development of a needs-based extension programme. The case organisation had modified the traditional extension programme planning process to involve stakeholders at different levels of participation. Similarly, the case organisation involved stakeholders in its multilevel monitoring and evaluation processes. Stakeholder participation in planning and evaluation, although aimed ultimately at efficient and effective programme implementation and improvement, did enhance accountability. Because the case organisation had taken on a broader livelihood security focus to extension, the definition of farmer needs was extended to encompass on-farm and off-farm needs that have impact on the contribution agriculture makes to the livelihood security of farm households in the district. This broader livelihood security focus to extension required the case organisation to take on additional roles from those it traditionally held. In the study, a typology of such roles was developed and a role selection process used by the case organisation during its programme planning process was described. Similarly, because of this broader focus, the case organisation had to work both across sectors and with other extension providers from within the sector to meet the needs of farmers. Again, the multistakeholder programme planning process was central to fostering coordination and collaboration amongst the various extension providers in the district. Decentralisation has placed greater managerial responsibility on management staff of the case organisation. In addition, the livelihood security focus has required technical staff and attitudinal changes to develop and seek for a much broader range of skills and knowledge - meaning that the development of both managerial and technical capacity was important for the case organisation. Needs-based training, the development of a learning environment and the enhancement of staff motivation were critical for the development of staff capacity. As with other extension organisations in developing countries, the funding for the case organisation was limited and uncertain. To overcome these constraints, the case organisation had in place mechanisms to ensure its resources were used efficiently and that it could mobilise additional resources from outside the organisation. Resource efficiency was improved through an intensive monitoring system and the use of stable needs-based groups. Additional resources were mobilised by lobbying government and international donors for funds for projects that would meet the needs of farmers. Further resources were obtained through collaboration with other stakeholder organisations. Again, the multistakeholder planning process provided a platform for collaboration. Networking and special issue forums also provided mechanisms for enhancing collaboration within the district. Decentralisation was introduced into Ghana in 1997 with the aim of eventually developing a demand-driven extension system. Although viewed as successful, the case organisation has yet to achieve the level of farmer participation (i.e. self-mobilisation) that is required for a demand-driven extension system. Currently, after six years of decentralisation, the level of farmer participation can be classified as somewhere between consultation and collaboration. Therefore, the results of this study suggest that the transition from a top-down to a demand-driven extension system will take considerable time and resources.
Keywords: Agricultural extension; Agriculture and state; Ghana; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300900 Land, Parks and Agriculture Management::300901 Farm management, rural management and agribusiness